LifeWatch ERIC Strategic Working Plan Outcomes - Christos Arvanitidis; Alberto Basset; Peter van Tienderen; Cristina Isabel Huertas Olivares; Cristina Di Muri; Lucas de Moncuit; Wouter Los (Research Ideas and Outcomes, 2024)
LifeWatch ERIC has embarked on its new destination towards upgrading and (co-)constructing its Infrastructure as a response to the needs of its target communities and stakeholders. Through an industrialisation process, all independent data, software components, publications and other types of research products contributed by the Member Countries will be consolidated and integrated to enable collaborative development. The Technology Readiness Level of LifeWatch ERIC will be raised to level 9. This process is described in its new Strategic Working Plan on its second implementation period (2022-2026). Accordingly, this topical collection of papers includes articles which describe the main outcomes, that is the deliverables of this new Strategic Working Plan. The deliverables published in this topical collection are not of a confidential nature and are developed in the form of a standard, structured template.